The Study of Age and Sex Frequency of Epilepsy, and It\'s Relating Factors in Epileptic Patients Refered to Sina and Ghaem Hospital in Hamadan City (1986-1995) - Ali Akbar Rezaei; Shahriar Saeedi (University of Social Welfare and Rehabilitation Sciences, 2000)
Objective: The epilepsy disease as one of common neurological diseases in all of communities has a specific significance. One of the helping factors to diagnosis and treatment of this disease is 10 identify prevalence and other effective factors of epilepsy. In this research, the main objective is determination of sex and age distribution of epilepsy, and also it's relating factors. Materials & Methods: This research is a descriptive retrospective study from 1989 to 1995. We studied 290 records of admitted epileptic patients. After designing a form, we gathered the data and then computed statistics and drew tables and diagrams. Results: Epilepsy disease was more common in males than females and the most common age was 11-20 years old. The most 'common age of beginning epilepsy was 2-10 years old In the predisposing factors, cerebral disease and febrile convulsion were more common than others. Conclusion: Since epilepsy is a disease with long duration of treatment, knowing the predisposing factors help to a successive treatment.